Trade between Algeria and the European Union - MESBAHI , Fatima Zahra (Finance and Business Economies Review, 2020)
International trade theories present trade as a solution to maximize the welfare of the nation. They are currently characterized by regional agreements, or bilateral agreements. Algeria, which is relatively well endowed with labor, and certain natural resources (gas, oil), essentially trade with the European Union, which is relatively well endowed with capital. So it is beneficial for Algeria to specialize in the production of the goods needed for labor, and to import goods endowed with capital from Europe. In order to try to analyze these questions we will present in the first part the trade of Algeria with the EU, which we will see the structure of trade, and understand the role of oil in these exchanges.